READINESS OF SENIOR STUDENTS FROM THE CARPATHIAN TERRAIN TO CHOOSE TEACHING PROFESSION: PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS - Tetyana Blyznyuk (Vasyl Stefanyk Precarpathian National University, 2015)
The article presented at the conference is the study of the problems of upbringing and education of senior pupils from the Carpathian mountain area. Namely the author investigates the students' readiness for choosing the teaching profession and willingness to work at rural mountain schools. Despite the big number of teachers in the labor market of Ukraine, now the system of education meets an acute issue dealing with the selection to the pedagogical specialties talented creative young people who actually choose teaching profession by nature and strong personal will. Today there are very few teachers whose level of commitment to perform professional duties in Ukrainian education is really high, and this is especially true about mountain school teachers. This phenomenon can be partially explained by the fact that teaching profession has low prestige in our society for the recent decades (Ukrainian teachers are not well-paid, their working conditions in rural Carpathian schools leave much to be desired). Therefore the problem of readiness of high school students to perform professional-pedagogical duties is of particular relevance. The author analyzes the psychological and pedagogical basis of the presented problem, defines the essence and structure of the notion "readiness for choosing the teaching profession". In the context of solving this issue one of the important conditions the author considers the comprehensive development of senior school students, particularly the development of their creative abilities.